LANGKAH TAKTIS GAYA KEPEMIMPINAN GUBERNUR BALI I WAYAN KOSTER DALAM PENCEGAHAN PENYEBARAN COVID-19 DI PROVINSI BALI - Nrangwesthi Widyaningrum; Hayatul Khairul Rahmat; Syamsul Maarif (Jurnal Manajemen Bencana (JMB), 2020)
This paper will discuss how the tactical steps of the leadership style of the Governor of Bali I Wayan Koster in an effort to prevent the spread of COVID-19 in the Province of Bali. This paper uses a library approach. The findings of this study are that the tactical steps taken by the Governor of Bali were quite fast and precise by mobilizing the provision of adequate health facilities and competent medical personnel to empower local wisdom so as to suppress the spread of COVID-19. The leadership style he shows is also quite interesting, namely through a participatory leadership style approach and a transformational leadership style in dealing with this pandemic. Where this leadership style is shown by leadership that is able to encourage innovative thinking and use the moral values of its followers as important to increase their awareness of a problem.